Analisis Sistem Diskrit pada Antrian Servis Bengkel Mobil di Honda Auto Serang - Heru Winarno; M.Bob Anthoni; Syaina Ulfah A; Rosihin Rosihin; Arvio Jihana Putra (Jurnal Rekayasa Proses dan Industri Terapan, 2025)
Honda Auto Serang is a car sales and maintenance company in Serang City. As car sales increase, the need for vehicle maintenance and repairs will also increase. Therefore, it is necessary to analyze the vehicle repair process queue system at the workshop. The analysis was conducted using Arena Software to determine the condition of the existing queue system and suggestions for improvements that can be provided to reduce the waiting time for the repair process. By organizing the repair process flow, providing complete work equipment and arranging spare part collection, the average waiting time for service advisors in the queue system on weekdays decreased from 21 minutes to 25 minutes in scenario 1 and 15 minutes in scenario 2. The average waiting time for service queue customers on weekdays was 97 minutes, reduced to 81 minutes in scenario 1 and 83 minutes in scenario 2.